Incubation Hub: a 'new' school for artisans where architectural innovation meets education in South Africa - Scott, Lee-Anne (My University, 2014)
In South Africa there are approximately three million people between the ages of 18 and 24 who are unemployed or not part of an education or training institute. There are residing issues concerning education in post-apartheid South Africa, such as poor quality education in areas where the socio-economic climates still prove challenging and an increasing absence of educational institutions and training facilities. As a result, South Africa is suffering from a lack of skilled labour across all sectors of trade. In the Green Paper for Post-School Education and Training, published in 2012, the Department of Higher Education and Training (DHET) addresses the current issues around education in South Africa and indicates that part of the resolution is to form a “nexus between the formal education system and the workplace.” Both private and public sectors need to adopt new infrastructure to ensure a higher success rate for empowering South Africans through the provision of skills-based education. This thesis is about creating a ‘new’ school idea - The Incubation Hub - for artisans, where architectural technological innovation meets education in South Africa, opens up vocational opportunities and subsequently allows for economic growth. The ‘new’ school will not only create a stronger and a more advanced workforce for South Africa but aims to bridge the gap between the corporate sector and the education and political sectors. The Incubation Hub tackles the proposed matter by recognising the opportunity for an architectural intervention, whereby a literal and physical symbiotic relationship is formed between two buildings – each with a separate function and role in society and the economy - that unites their individual responsibilities to create a new identity. In doing so, the Incubation Hub aims to improve the social and economic status of South Africa on a local and global level.
This document is submitted in partial fulfilment for the degree: Master of Architecture [Professional] at the University of the Witwatersrand, Johannesburg, South Africa, in the year 2013.
Keywords: School buildings--South Africa--Design and construction; School facilities--Planning--South Africa; Schools--South Africa--Sociological aspects